Exploring Faculty Perceptions of AI Integration in Pedagogical Practices at Higher Education Institutions: : A Qualitative Study - gealone, dennis (International Journal of Arts, Sciences and Education, 2024)
Abstract The rapid advancement of artificial intelligence (AI) has significantly influenced higher education, with AI-driven tools increasingly being integrated into pedagogical practices. This study explores faculty members' perceptions of AI integration, examining their attitudes, concerns, and expectations regarding its implementation. Utilizing a qualitative research design, the study employs a phenomenological approach to capture the lived experiences of faculty members in higher education institutions. Data were collected through semi-structured interviews and focus group discussions, which were analyzed thematically. Findings reveal that faculty perceptions range from enthusiasm about AI’s potential to concerns regarding ethical implications, academic integrity, and the digital divide. While AI-driven tools enhance instructional efficiency, provide real-time feedback, and personalize learning experiences, challenges such as inadequate training, resistance to AI adoption, and concerns about student over-reliance on AI were identified. Faculty members emphasized the need for structured professional development, clear institutional policies, and a balanced AI-human instructional approach. This study provides valuable insights for higher education institutions seeking to optimize AI integration while ensuring academic integrity and instructional quality.